Metformin use and mortality in patients with advanced chronic kidney disease: national, retrospective, observational, cohort study. Issue 8 (August 2015) - Hung, Szu-Chun; Chang, Yu-Kang; Liu, Jia-Sin; Kuo, Ko-Lin; Chen, Yu-Hsin; Hsu, Chih-Cheng; Tarng, Der-Cherng
Summary Background Metformin is recommended as a first-line treatment for patients with type 2 diabetes. However, use of this drug has been contraindicated in individuals with impaired kidney function because of the perceived risk of lactic acidosis. Evidence now supports cautious use of metformin in people with mild-to-moderate chronic kidney disease. However, studies examining the use of metformin in patients with advanced chronic kidney disease are lacking. We aimed to assess the safety of metformin in patients with type 2 diabetes and advanced (approximately stage 5) chronic kidney disease. Methods We did a retrospective, observational, cohort study of patients with type 2 diabetes who were enrolled prospectively in Taiwan's national health insurance research database between Jan 1, 2000, and June 30, 2009, and had follow-up data until Dec 31, 2009. We included individuals with a serum creatinine concentration greater than 530 μmol/L, which is approximately equivalent to stage 5 chronic kidney disease. From a consecutive sample of 12 350 patients with type 2 diabetes and chronic kidney disease, 1005 used metformin and 11 345 were non-users. We matched users and non-users of metformin by propensity score in a 1:3 ratio. Our primary outcome was all-cause mortality. Findings 813 metformin users were matched by propensity score to 2439 non-users. The two groups of patients did not differ significantly by 30 baseline clinical and socioeconomic variables. Median follow-up in the matched cohort was 2·1 years (range 0·3–9·8). All-cause mortality was reported in 434 (53%) of 813 metformin users and in 1012 (41%) of 2439 non-users. After multivariate adjustment, metformin use was an independent risk factor for mortality (adjusted hazard ratio 1·35, 95% CI 1·20–1·51; p<0·0001). The increased mortality risk was dose-dependent and was consistent across all subgroup analyses. However, metformin use compared with no use was associated with a higher but non-significant risk of metabolic acidosis (1·6 vs 1·3 events per 100 patient-years; adjusted hazard ratio 1·30, 95% CI 0·88–1·93; p=0·19). Interpretation Use of metformin in people with type 2 diabetes and a serum creatinine concentration greater than 530 μmol/L is associated with a significantly increased risk of all-cause mortality compared with non-users. Metformin use should not be encouraged in this patient group. Funding Taipei Tzu Chi Hospital, Taipei Veterans General Hospital, Foundation for Poison Control, National Health Research Institutes, Ministry of Science and Technology of Taiwan.